Postdoctoral scientists are mentors, and it is time to recognize their work. - Gracielle Higino; Ceres Barros; Ellen Bledsoe; Dominique G Roche; Sandra Ann Binning; Timothée Poisot (PLoS Biology, 2023)
Academia often fails to recognize the important work that supports its functioning, such as mentoring and teaching performed by postdoctoral researchers. This is a particular problem for early-career researchers, but opportunities exist to improve the status quo.